2001
DOI: 10.1210/jcem.86.9.7847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcitriol or Calcium on Bone Mineral Density, Bone Turnover, and Fractures in Men with Primary Osteoporosis: A Two-Year Randomized, Double Blind, Double Placebo Study

Abstract: Osteoporosis in men is an emerging public health problem. As calcitriol reduces the rate of vertebral fractures in osteoporotic postmenopausal women, we conducted a prospective study of this treatment in men with primary osteoporosis. Our study was a 2-yr, randomized, double masked, double placebo-controlled trial of calcitriol (0.25 microg twice daily) or calcium (500 mg twice daily) in 41 men with primary osteoporosis and at least 1 baseline fragility fracture. Thirty-three men (85%) completed the study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 30 publications
(29 reference statements)
0
10
0
2
Order By: Relevance
“…The literature searches identified 6,475 records (citations) for review; 2,673 of these were excluded because they were duplicates (same citation found in different databases), leaving 3,802 unique records for review. Twenty‐four of these records reporting results for 22 different studies met inclusion criteria . Figure shows a flow diagram of the literature search and study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature searches identified 6,475 records (citations) for review; 2,673 of these were excluded because they were duplicates (same citation found in different databases), leaving 3,802 unique records for review. Twenty‐four of these records reporting results for 22 different studies met inclusion criteria . Figure shows a flow diagram of the literature search and study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Only two included studies performed head‐to‐head comparisons of drugs that the FDA has approved for men—one study that compared teriparatide with alendronate and another study that compared zoledronic acid with alendronate; neither of these studies reported RR of fracture outcomes. Most studies reported pharmaceutical company funding …”
Section: Resultsmentioning
confidence: 99%
“…In a 2‐year, randomized, double‐blind study of 33 patients with at least one osteoporotic fracture, Ebeling et al. [17] concluded that calcium supplementation (500 mg/day) did not prevent subsequent osteoporotic fractures to a significant extent. Dawson‐Hughes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of anti-fracture effectiveness, in fact, is weaker for other vitamin D analogues as compared with vitamin D 3 , while the risk of side effects is higher (13). Calcitriol (1,25(OH)2 vitamin D) for example, had no statistically significant effect on hip fracture, non-vertebral fractures or new vertebral deformities (13,18). Two trials suggested that vertebral fractures may be prevented by 1α-hydroxycalciferol (alfacalcidol).…”
Section: Type and Source Of Vitamin D: Metabolites Active Forms And mentioning
confidence: 99%